(untitled) - Kutner, Marc Leslie (Cambridge, 2003)
The book are generally clear and instructive, although the sections on subjects like nuclear and particle physics could be a little overwhelming to the uninitiated - it's simply a lot of information to present in a relatively small amount of space, but the author does a decent job
Keywords: Astronomy,Thiên văn học